Efficacy of video-based psychotherapy in reducing psychological distress of COVID-19 patients treated in isolation ward (Medical Journal of Indonesia, 2021)
BACKGROUND Hospitalized patients with COVID-19 experience isolation during treatment, which may cause psychological distress. Thus, alternative ways to deliver psychological support are needed when face-to-face therapy is not possible. This study aimed to investigate the efficacy of video-based psychotherapy in reducing distress in COVID-19 patients treated in an isolation ward. METHODS This quasi-experimental trial without a control group included 42 COVID-19 patients aged 20–59 years. Participants were recruited conveniently in the COVID-19 isolation ward in Cipto Mangunkusumo Hospital, Jakarta, Indonesia. They watched three brief psychotherapy videos including relaxation, managing thoughts and emotions, and mindfulness for approximately 30 min. The videos were created by the Department of Psychiatry, Faculty of Medicine, Universitas Indonesia. Subjective units of distress scale (SUDS) was measured before and after watching all videos. Data were analyzed using the Wilcoxon-signed rank test. RESULTS All 42 subjects finished watching the videos. 31 subjects experienced a significant median decrease in SUDS score after the intervention. The effect size of the psychotherapy videos for the SUDS score was 0.485 (95% CI 0.302 to 0.634). CONCLUSIONS Watching psychotherapy videos is effective in reducing the SUDS score for COVID-19 patients in an isolation ward. Our brief video-based psychotherapy intervention has reduced psychological distress in hospitalized COVID-19 patients with limited access to face-to-face consultations due to the risk of disease transmission.